Tapered Roller Bearings Cage to Improvement Design - Zhao Xiuting; Liang Li; Liu Zhiwen (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In order to improve the utilization of materials, improving stamping cage processing methods, the single row tapered roller bearing cage is improved from structural strength, puts forward whole stamping cage a type of structure. Use ANSYS finite element analysis to the different structure and the thickness cage. Get the stress contours of the cage, based on equal strength design principles. Get sheet metal stamping manufacturing cage, improving the process and precision manufacturing. Change the traditional increase cage strength only by increasing the thickness of the method. Improve production efficiency and reduce the input device. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4661